2014
DOI: 10.1098/rspa.2014.0168
|View full text |Cite
|
Sign up to set email alerts
|

Linear theory for filtering nonlinear multiscale systems with model error

Abstract: In this paper, we study filtering of multiscale dynamical systems with model error arising from limitations in resolving the smaller scale processes. In particular, the analysis assumes the availability of continuous-time noisy observations of all components of the slow variables. Mathematically, this paper presents new results on higher order asymptotic expansion of the first two moments of a conditional measure. In particular, we are interested in the application of filtering multiscale problems in which the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 58 publications
(211 reference statements)
1
54
0
Order By: Relevance
“…A more challenging and realistic setting would be one where the full model is unknown, and one has to use noisy observations to infer a parametrization (Li et al 2009;Berry and Harlim 2014;Harlim 2016). This is the challenging topic of parameter estimation for hidden Markov and non-Markov models (Kantas et al 2009).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more challenging and realistic setting would be one where the full model is unknown, and one has to use noisy observations to infer a parametrization (Li et al 2009;Berry and Harlim 2014;Harlim 2016). This is the challenging topic of parameter estimation for hidden Markov and non-Markov models (Kantas et al 2009).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Examples include deterministic and stochastic parametrization methods (Palmer 2001;Meng and Zhang 2007;Berry and Harlim 2014;Mitchell and Carrassi 2015), additive random perturbations (Hamill and Whitaker 2005;Houtekamer et al 2009), low dimensional method (Li et al 2009), and averaging and homogenization methods (Pavliotis and Stuart 2008;Mitchell and Gottwald 2012;Gottwald and Harlim 2013). Representations of the model error can be derived either within data assimilation using the noisy observations, or before data assimilation using noiseless training data.…”
Section: Introductionmentioning
confidence: 99%
“…We should point out that if we fix these two parameters to be those from the Mori-Zwanzig projection and run the filtering procedure to estimate the remaining parameters, a,b,σ 1 ,R, the resulting estimates are completely innaccurate. This suggests that while the perturbation approach [16] suggests the explicit forms of the reduced model, it is more natural to adaptively estimate all the parameters which reconfirms the results in [37]. Moreover, in general, there can be nonunique parameters that provide the same equilibrium statistics (for e.g., see Proposition 1(d) in [26]).…”
Section: Numerical Results On Parameter Estimation Of Models With mentioning
confidence: 76%
“…In general problems, however, the success of this modeling approach will depend mostly on the choice of the ansatz for modeling the memory terms. As it has been theoretically established in [37], if the ansatz is adequate, then it is possible to obtain, both, accurate climatological statistical forecasting and optimal filtering. Our NLS example in this paper empirically suggested that our ansatz is optimal in this case.…”
Section: Numerical Results For Multiple Retained Fourier Modesmentioning
confidence: 99%
See 1 more Smart Citation